Pengelolaan Ecobrick Sebagai Alternatif Untuk Mengurangi Volume Limbah Plastik di Desa Kersik - Dion Saputra; Jidan Ramadhan Hadi; Wira Bharata; Khairil Anwar; Poppy Alvianolita Sanistasya; Muhammad Zaini (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Ecobrick management as an alternative to reduce the volume of plastic waste in Kersik Village. This research aims to explore the potential for using Ecobricks as an innovative solution in reducing the volume of plastic waste in Kersik Village. The PAR (Participatory Action Research) method uses the 5T approach (To Know, To Understand, To Plan, To Action, To Reflection). This approach is not only used to understand problems in society, but also to plan, act and reflect on the actions taken. It is hoped that the results of this research can contribute to further understanding of environmental sustainability at the local level, while providing a practical view regarding the application of Ecobricks as a sustainable strategy to reduce the negative impact of plastic waste on the Kersik Village community.